Dysregulated Immunity in Pulmonary Hypertension: From Companion to Composer - Funk-Hilsdorf, Teresa C.; Behrens, Felix; Grune, Jana; Simmons, Szandor (Frontiers in Physiology, 2022)
Pulmonary hypertension (PH) represents a grave condition associated with high morbidity and mortality, emphasizing a desperate need for innovative and targeted therapeutic strategies. Cumulative evidence suggests that inflammation and dysregulated immunity interdependently affect maladaptive organ perfusion and congestion as hemodynamic hallmarks of the pathophysiology of PH. The role of altered cellular and humoral immunity in PH gains increasing attention, especially in pulmonary arterial hypertension (PAH), revealing novel mechanistic insights into the underlying immunopathology. Whether these immunophysiological aspects display a universal character and also hold true for other types of PH (e.g. PH associated with left heart disease (PH-LHD)), or whether there are unique immunological signatures depending on the underlying cause of disease are points of consideration and discussion. Inflammatory mediators and cellular immune circuits connect the local inflammatory landscape in the lung and heart through inter-organ communication, involving e.g., the complement system, sphingosine-1-phosphate (S1P), cytokines and subsets of e.g. monocytes, macrophages, natural killer (NK) cells, dendritic cells (DCs), and T- and B-lymphocytes with distinct and organ-specific pro- and anti-inflammatory functions in homeostasis and disease. Perivascular macrophage expansion and monocyte recruitment have been proposed as key pathogenic drivers of vascular remodeling, the principal pathological mechanism in PAH, pinpointing towards future directions of anti-inflammatory therapeutic strategies. Moreover, different B- and T-effector cells as well as DCs may play an important role in the pathophysiology of PH as an imbalance of T-helper-17-cells (TH17) activated by monocyte-derived DCs, a potentially protective role of regulatory T-cells (Treg) and autoantibody-producing plasma cells occur in diverse PH animal models and human PH. This article highlights novel aspects of the innate and adaptive immunity and their interaction as disease mediators of PH and its specific subtypes, noticeable inflammatory mediators and summarizes therapeutic targets and strategies arising thereby.